State-of-the-Art Exercise Concepts for Lumbopelvic and Spinal Muscles – Transferability to Microgravity - Hides, Julie; Hodges, Paul; Lambrecht, Gunda (Frontiers in Physiology, 2019)
Low back pain (LBP) is the leading cause of disability worldwide. Over the last three decades, changes to key recommendations in clinical practice guidelines for management of LBP have placed greater emphasis on self-management and utilisation of exercise programmes targeting improvements in function. Recommendations have also suggested that physical treatments for persistent LBP should be tailored to the individual. This mini review will draw parallels between changes which occur to the neuromuscular system in microgravity and conditions such as LBP which occur on Earth. Prolonged exposure to microgravity is associated with both LBP and muscle atrophy of the intrinsic muscles of the spine, including the lumbar multifidus. The finding of atrophy of spinal muscles has also commonly been reported in terrestrial LBP sufferers. Studying astronauts provides a unique perspective and valuable model for testing the effectiveness of exercise interventions which have been developed on Earth. One such approach is motor control training which is a broad term which can include all the sensory and motor aspects of spinal motor function. There is evidence to support the use of this exercise approach, but unlike changes seen in muscles of LBP sufferers on Earth, the changes induced by exposure to microgravity are rapid, and relatively consistent in nature. Drawing parallels between changes which occur to the neuromuscular system in the absence of gravity and which exercises best restore size and function could help health professionals tailor improved interventions for terrestrial populations